Fifty Years of Forestry in Tripura - Achievements in Retrospect, Macro Futuristic Perspectives and Imperatives - Ray, P. N. (Indian Forester, 1998)
Achievements during last 50 years of forestry in Tripura have been documented, highlighting notable developments in forest resources base, afforestation, infrastructure, control of shifting cultivation, conservation efforts, enabling mechanisms, capacity building and institutional strengthening. A critical appreciation reveals that gains accrued but disappointments were also many. It evaluates the efficacies ofimplementation of National Forest Polices, management planning process, conservation, social forestry, commercial function, protection, regulation and enforcement works pointing out the issues where forestry orgainsation could not achieve certain cherished goals and why; several institutional shortcomings, external constraints and organisational weakness are identified. Within the general framework of managerial cybernetics, strategic planning of forestry in the State is devised on the basis of a SWOT analysis spelling out the ways and means of capitalising the latent strengths and neutralising the threats in the external environment, and coping up micro environmental complexity. The imperatives of a mission-driven forest management in the State facing the emerging challenges, have been suggested.